2017
DOI: 10.1136/bmjoq-2017-000158
|View full text |Cite
|
Sign up to set email alerts
|

Reducing patient mortality, length of stay and readmissions through machine learning-based sepsis prediction in the emergency department, intensive care unit and hospital floor units

Abstract: Introduction Sepsis management is a challenge for hospitals nationwide, as severe sepsis carries high mortality rates and costs the US healthcare system billions of dollars each year. It has been shown that early intervention for patients with severe sepsis and septic shock is associated with higher rates of survival. The Cape Regional Medical Center (CRMC) aimed to improve sepsis-related patient outcomes through a revised sepsis management approach. Methods In collabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 26 publications
2
116
0
1
Order By: Relevance
“…A recent trial across two surgical ICUs with 142 patients (75 controls) reported a 2.7-day reduction in the length of stay (P ϭ 0.04) and a 12% reduction in in-hospital mortality (P ϭ 0.02). Another study, reporting a 4-month experience in a 242-bed acute-care hospital, demonstrated a reduction in the length of stay of 0.43 days, along with a reduction in the mortality rate by 60.24% and a reduction in the rate of sepsis-related 30-day readmission, by 50%, postimplementation (215). Across these two studies, the algorithm score had a sensitivity and a specificity of 0.83 and 0.96, respectively, for sepsis.…”
Section: Beyond Rule-based Decision Support: Power Of Electronic Medimentioning
confidence: 99%
“…A recent trial across two surgical ICUs with 142 patients (75 controls) reported a 2.7-day reduction in the length of stay (P ϭ 0.04) and a 12% reduction in in-hospital mortality (P ϭ 0.02). Another study, reporting a 4-month experience in a 242-bed acute-care hospital, demonstrated a reduction in the length of stay of 0.43 days, along with a reduction in the mortality rate by 60.24% and a reduction in the rate of sepsis-related 30-day readmission, by 50%, postimplementation (215). Across these two studies, the algorithm score had a sensitivity and a specificity of 0.83 and 0.96, respectively, for sepsis.…”
Section: Beyond Rule-based Decision Support: Power Of Electronic Medimentioning
confidence: 99%
“…One clinical validation study in the ED showed the machine learning model outperformed manual scoring by nurses and the SIRS criteria when identifying severe sepsis and septic shock [28], the other study made no comparison [29]. The interventional studies included two pre-post implementation studies (in-hospital) [30,31] and one ICU randomized controlled trial [32]. All looked at mortality and hospital length of stay, but results are mixed as shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Common methods include linear regression (n ¼ 2), 8,9 logistic regression (n ¼ 5), 10-14 support vector machines (n ¼ 4), [15][16][17][18] Markov models (n ¼ 4), [19][20][21][22] and Bayesian networks (n ¼ 2). 23,24 Additionally, a few studies (n ¼ 6), [25][26][27][28][29][30] used an industry created tool, InSight (Dascena Inc.), to validate performance compared with the more commonly used methods. In particular, Mao et al, used InSight to test the predictive abilities of the industrycreated sepsis detection algorithm on open source and local data sets, determining the transferability of the algorithm across varying data sets.…”
Section: Variability In Machine Learning or Modeling Techniquesmentioning
confidence: 99%
“…Many studies used publicly available data sets, such as Medical Information Mart for Intensive Care (MIMIC) (n ¼ 8), 8,12,19,[25][26][27][28]32 or the less commonly used Medical Data Warehousing and Analysis (MEDAN) project 18,34 These data sets are extensive and provide researchers with real, de-identified data that can be used as testing, training, or validation sets when using predictive analytics. Additionally, many studies (n ¼ 22) used ICU data (either local 14,17,[20][21][22][23][29][30][31][35][36][37] or MIMIC), while nine studies used ED [9][10][11]13,15,16,24,38,39 data. While local data varied greatly in size, ranging from 24 to 198,833, some used MIMIC in addition to their local data sets, which created a potentially more generalizable set of data to increase statistical significance and to increase the transfer of learning.…”
Section: Variability In Data Sample Selection and Sizementioning
confidence: 99%